Puerperal Fever and Neonatal Pleural Empyema and Bacteremia Caused by Group A Streptococcus - Laurance Lequier; Wendy L Vaudry (Canadian Journal of Infectious Diseases)
A term neonate developed early onset of sepsis and pleural empyema with group A streptococcus. Her mother also became septic with group A streptococcus in the early postpartum period. The infant required initial chest tube drainage. After reaccumulation of pleural fluid after removal of the chest tube, a thoracotomy with decortication was performed. The isolates of group A streptococcus were analyzed and found to be identical serotypes of the same bacterium. The serotyping revealed both to be M type 1, T pattern 1. Polymerase chain reaction detected the genomic sequence for streptococcal pyrogenic exotoxin A and B in both isolates. With the increase in invasive streptococcal infections in the community, serious perinatal infections may become more frequent.